Thermal comfort and energy related occupancy behavior in Dutch residential dwellings - Anastasios Ioannou (A+BE: Architecture and the Built Environment)
Residential buildings account for a significant amount of the national energy consumption of all OECD countries and consequently the EU and the Netherlands. Therefore, the national targets for CO2 reduction should include provisions for a more energy efficient building stock for all EU member states.